PENYULUHAN DAN PELATIHAN KOSAKATA BAHASA INGGRIS TENTANG CUCI TANGAN ENAM LANGKAH SEBAGAI UPAYA PENINGKATAN PERILAKU HIDUP BERSIH DAN SEHAT DI PAUD ALIEF PALEMBANG - Desliyanah, Sherly; Afriyani, Rahmalia; Wagisri, Wagisri (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2026)
This community service activity aimed to improve young children's understanding of clean and healthy living behaviors through the practice of the six-step handwashing method while introducing English vocabulary related to the activity. The activity was conducted at PAUD Alief Palembang and involved 25 students as participants. The method used in this activity consisted of counseling and training carried out through several stages, namely preparation, problem identification, planning, implementation, and evaluation. The materials delivered included the importance of maintaining hand hygiene, the practice of the six-step handwashing procedure based on health standards, and the introduction of English vocabulary related to handwashing activities. The results showed an increase in students’ understanding after participating in the activity. Before the implementation, only 32% of students were able to mention English vocabulary related to handwashing and 28% were able to practice the six steps of handwashing correctly. After the activity, the percentages increased to 84% for English vocabulary mastery and 88% for the ability to practice the handwashing steps correctly. These results indicate that counseling and training methods using an interactive approach are effective in improving students’ understanding of clean and healthy living behavior as well as introducing English vocabulary to early childhood learners.